Children of the Golden Horse - Pelz, Claudia (Italy, 2007)
Ten-year old Jattae is a so-called "Hilltriber", one of over 100,000 members of ethnic minorities currently settled in the mountains of North Thailand. Under Thai law these nomadic peoples do not have citizenship, and are prevented from farming using their traditional methods. Consequently most, like Jattae, live in poverty, with many turning to drugs and prostitution. An invitation to join a Buddhist Temple offers Jattae a chance to escape such a fate
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films